Influence of personal factors pilgrimage tour operators’ marketing mix strategies on tourist satisfaction in a religious tourism setting - Mohd Radzi, Ras Afirina (2021)
Marketing mix strategies has received a great deal of attention in the past. However, less attention was given towards understanding Umrah tour packages. Additionally, research on tourism, personal factors, and marketing mix strategies of pilgrimage tour operators are still restricted in the current situation. Hence, the study proposed to determine the factors influencing satisfaction of pilgrimage tourists based on the Consumer Behaviour Model. Modifications were made to the model based on the fundamental premises linked to the current study. Data collection was conducted through online social media platform groups to target the exact respondents. A total of 170 quantitative valid questionnaires were collected from the survey using convenient sampling. SPSS 25 was applied for data analysis where descriptive, regression analysis, analysis of variance (ANOVA), and moderation analysis verified the hypothesis developed. The study contributes to theoretical knowledge by contributing to the literature regarding the usefulness of profiling respondents, marketing mix strategy, motivation, and Umrah tourist satisfaction. The study also benefits practitioners, academicians, especially Umrah tour operators in understanding the needs and wants of Umrah pilgrims as well as ways to improve their marketing mix strategies.